Post-translational Modifications of bZIP Transcription Factors in Abscisic Acid Signaling and Drought Responses - Joo, Hyunhee; Baek, Woonhee; Lim, Chae W.; Lee, Sung Chul (Current Genomics, 2021)
Under drought stress, plants have developed various mechanisms to survive in the reduced water supply, of which the regulation of stress-related gene expression is responsible for several transcription factors. The basic leucine zippers (bZIPs) are one of the largest and most diverse transcription factor families in plants. Among the 10 Arabidopsis bZIP groups, group A bZIP transcription factors function as a positive or negative regulator in ABA signal transduction and drought stress response. These bZIP transcription factors, which are involved in the drought response, have also been isolated in various plant species such as rice, pepper, potato, and maize. Recent studies have provided substantial evidence that many bZIP transcription factors undergo the post-translational modifications, through which the regulation of their activity or stability affects plant responses to various intracellular or extracellular stimuli. This review aims to address the modulation of the bZIP proteins in ABA signaling and drought responses through phosphorylation, ubiquitination and sumoylation.
Keywords: drought resistance